Metformin-letrozole in comparison with Metformin-clomiphene citrate in clomiphene-resistance PCOS patients undergoing IUI - Mohammad Hossein Fallahzadeh; Mojgan Javedani; Robab Davar (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2011)
Background: Polycystic ovary syndrome (PCOS) is associated with approximately 75% of women who suffer from infertility due to anovulation. Additionally, around 20- 25% of anovulatory women with PCOS do not respond at all to clomiphene citrate and are considered to be "clomiphene- resistant". Aromatase inhibitors have been suggested as an alternative treatment to clomiphene as the discrepancy between ovulation and pregnancy rates with clomiphene citrate has been attributed to its anti-estrogenic action and estrogen receptor depletion. Objective: The aim of this study is to compare results of Metformin-letrozole with Metformin-clomiphene citrate in clomiphene resistance PCOS patients undergoing IUI.Materials and Methods: In this single blind randomized trial, ovarian cycles were studied in 100 clomiphene- resistant patients with PCOS. The inclusion criteria were patients who received 150mg clomiphene citrate daily for 3 cycles and failed to become pregnant. The patients were matched for their age, body mass index (BMI), and infertility period. They were randomly allocated to a metformin-letrozole group (n=50) and a metformin-clomiphene citrate group (n=50). Chemical and clinical pregnancies were assessed after IUI. Abortion rates were determined in both groups. Results: Regarding pregnancy rate, there was no significant difference between the two groups. One miscarriage (2%) occurred in the metformin-clomiphene citrate group, whereas none was seen in the metformin-letrozole group. Conclusion: There is no significant difference in pregnancy rate between clomiphene citrate and letrozole groups although it has been 2% in the former and 5% in the latter.